No book to call one’s own: Perspectives on translation and literary creation in Francesca Duranti’s The House on Moon Lake - Feltrin-Morris, Marella (Linguistica Antverpiensia, New Series – Themes in Translation Studies, 2021)
Francesca Duranti ’s prize-winning novel The House on Moon Lake (La casa sul lago della luna, 1984) has been hailed by various critics as an intriguing concoction of reality and illusion. However , the story ’s main dichotomy seems to be between translation as frustrated desire for possession, and original writing as more fulfilling ownership of the text. The fact that even the possession of a text on the part of its author ultimately proves to be ephemeral does not chan ge the image of translation with which Duranti presents the reader: a mechanical transfer of words, a cowardly, unimagi-native anta gonist to ‘true’ literary creation. This essay examines the ways in which this portrayal is carried out in the text, and its implications in a per-spective on translation that perpetuates notions of weakness and passivity as its defining characteristics.